2017
DOI: 10.1186/s40729-017-0107-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel expandable short dental implants in situations with reduced vertical bone height—technical note and first results

Abstract: PurposeShort implants often have the disadvantage of reduced primary stability. The present study was conducted to evaluate the feasibility and safety of a new expandable short dental implant system intended to increase primary stability.MethodsAs a “proof of concept”, a prospective clinical cohort study was designed to investigate intraoperative handling, primary and secondary implant stability (resonance frequency analysis), crestal bone changes, implant survival and implant success, of an innovative short e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Implant positions, prosthetic treatments, and success rates are summarized in Table 3 . This table also contains nine patients (indicated by “#”) whose short-term results have previously been published [ 24 ]. In terms of validating the initial outcome, these individuals are included in the present analysis because of long-term follow-up.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Implant positions, prosthetic treatments, and success rates are summarized in Table 3 . This table also contains nine patients (indicated by “#”) whose short-term results have previously been published [ 24 ]. In terms of validating the initial outcome, these individuals are included in the present analysis because of long-term follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…The implant was submitted to all mechanical fatigue tests in vitro (ISO 14801:2016 standard and FDA guidance for root-form endosseous dental implants and endosseous dental implant abutments). Apical expansion was performed after implant insertion using a special expansion tool and ratchet torque, which resulted in a pyramid shape [ 24 ]. The implants had the following dimensions and special characteristics: 5 mm, 6 mm, and 7 mm in length; 3.75 mm and 4.1 mm in diameter; internal (7 mm length) or external (5 mm and 6 mm length) hexagon platform.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reich et al ( 23 ) reported 66.9 ± 8.9 ISQ in 5-7mm long implants placed in D3 and D4 bone of the maxilla. These results are similar to those obtained in D3 bone for PHIA/SHORT-I (66.43 ± 4.49 ISQ) short implants of our study.…”
Section: Discussionmentioning
confidence: 99%